Integrating renewable energy solutions to reduce carbon footprints and support global environmental sustainability - Safaria, Albert; Pramono, Sholeh Hadi; Khusaini, Moh. (Jurnal Konseling dan Pendidikan, 2025)
Increasingly worrying global climate change drives the need to transition to renewable energy as a key strategy in reducing carbon footprint and supporting environmental sustainability. Fossil fuel-based energy has become a major contributor to the increase in greenhouse gas emissions, so more environmentally friendly and sustainable solutions are needed. Various studies have shown that the integration of renewable energies, such as solar, wind, and biomass, has great potential in reducing carbon emissions and improving energy efficiency globally. However, the implementation of renewable energy still faces challenges in terms of technology, policies, and investments that are not yet optimal. This study aims to evaluate the effectiveness of the integration of renewable energy solutions in reducing the carbon footprint as well as analyze the factors that affect the success of its implementation. The method used in this study is a literature study, by analyzing various scientific journals, policy reports, and previous research results that discuss the green energy transition and its impact on the environment. A thematic analysis approach is used to identify key patterns in the research that has been conducted. The results show that the use of renewable energy is able to significantly reduce carbon emissions by up to 50% in several industrial and transportation sectors. In addition, strong policy support, such as tax incentives and investment in green infrastructure, are important factors in the successful adoption of renewable energy. Thus, an integrative strategy is needed that includes technological innovation, supportive policies, and the involvement of various stakeholders to accelerate the transition to a more sustainable energy system.